Novos potenciais antivirais inibidores de serina protease derivados do isomanídeo e estatina - Zorzanelli, Bruna Costa (2013)
This work shows a new and efficient synthetic route for obtaining unpublished peptidomimetic derivatives from isomannide and statin core as potential inhibitors of NS3 serine protease enzyme presents in dengue and hepatitis C virus. Three sets were synthesized in good yields: esters (42a-c), acids (43a-c) and amides (44a-c), which were characterized by NMR and IR and tested by in vitro inhibition of HCV NS3 protease. The acid 43c, derived from the proline amino acid, was the most active compound showing 90-95% of viral enzymatic activity inhibition.